Relationship between oral health status and nutritional status in a group of older persons: denture status - Phetchan, Ratthawit; Sinavarat, Potchaman; Anunmana, Chuchai; Kanchanavasita, Widchaya (Mahidol Dental Journal, 2020)
Objective: The aim of the study was to investigate the effects of tooth loss, denture replacement, and denture status, i.e. retention, stability, occlusion and defect on nutritional status in the pre-ageing and ageing people residing at home. Materials and Methods: This cross-sectional study was conducted in a rural area, northern Thailand. The study population (290 persons) comprised free living participants aged 50 years or more. Subjects (115 persons) aged 50-59 were the pre-ageing group and individuals (175 persons) aged 60 and over were the ageing group. Subjects had interviews, oral examinations, and denture examinations. The Short-Form Mini-Nutritional Assessment (MNA-SF) was used to assess nutritional status. Association between dentition status, denture status, and nutritional status were analyzed using Chi-square test and Fisher’s exact test. Results: Fifteen participants (13%) in the pre-ageing group and 50 participants (28.7%) in the ageing group used removable dentures. Among the participants who used dentures, all participants in the pre-ageing (15 persons) wore partial dentures while 36 participants (20.6%) in the ageing group wore partial dentures and 14 participants (8.0%) wore complete dentures. The results revealed that the state of tooth loss without denture replacement resulted in the lowest MNA-SF score in both pre-ageing and ageing groups. Higher scores were achieved in persons with removable denture replacement while persons with adequate dentition had the highest scores. The association between dentition status and nutritional status in the pre-ageing group was not found, but the statistically significant association existed in the ageing group (p<0.05). Additionally, the association between the denture status and nutritional status in both pre-ageing and ageing participants were not found (p>0.05). Conclusion: To improve the quality of life of older persons, oral hygiene care and appropriate dental treatments should be emphasized to maintain natural dentition and prevent tooth loss. This strategy should be started before those adults reach their old age. In addition, dentists should provide appropriate dietary advice to denture wearers, especially in the ageing group, and encourage them to eat various foods by proper preparing so that they can have adequate nutrient content.